Development and Validation of an Innovative Stability Indicating Method Using UVSpectroscopy Techniques for Ritonavir in Bulk Drug and Pharmaceutical Dosage Forms: Pharmaceutical Science-Pharmaceutical Analysis - Sai Venkata Nagendra Abhay Raj, Gurram; Mondal, Sumanta; Chakraborty, Subhadip; Ghosh, Moumita (International Journal of Life Science and Pharma Research, 2023)
Ritonavir is a protease inhibitor used to treat HIV/AIDS. It is seldom employed for its antiviral activity but instead as a booster for other protease inhibitors. Our study’s significant objective is to develop a new, simple, accurate, precise, and reproducible UV spectrophotometric approach for investigation by apotheosis to analyze ritonavir. Three alternative simple, accurate, and precise UV spectrophotometric techniques-the, zero-order (method A), first-order (method B), and the area under the curve (method C) spectrophotometric methods have been established for the measurement of ritonavir in bulk and pharmaceutical dosage. The drug was dissolved in ethanol, and then 0.063 M Phosphate buffer solution (pH 7.0), and the observed λmax are 271 nm for the zero-order spectrophotometric method (method A), 258 nm for the first-order spectrophotometric method, 260–281 nm for the area under the curve spectrophotometric method (method C). Under the optimum conditions, linear relationships with good correlation coefficients 0.9994–0.9999 were found between the reading and the corresponding concentration of the drug in the range of 10-50 μg/ml. The proposed methods can detect the analyte in the lower limits of 0.24 to 0.38 μg/ml. The precision of the methods was satisfactory, and the percentage relative standard deviation values did not exceed 2%. The proposed methods were successfully applied to the analysis of ritonavir in its bulk and commercial formulations with good repeatability and reproducibility; the label claim percentages ranged from 99.56 to 99.64 ± (0.34-0.63) % w/v. The research findings of the current approach were shown to be more accurate and trustworthy for ritonavir in pharmaceutical dosage forms and bulk pharmaceuticals compared to those previously reported by the spectrophotometric approaches. The proposed techniques can be used for routine inspections without causing any interference from excipients or other substances because of the quick and repeatable analysis.